2020
DOI: 10.1051/0004-6361/202038695
|View full text |Cite
|
Sign up to set email alerts
|

Spin-orbit alignment and magnetic activity in the young planetary system AU Mic

Abstract: We present high-resolution near-infrared spectropolarimetric observations using the SPIRou instrument at Canada-France-Hawaii Telescope (CFHT) during a transit of the recently detected young planet AU Mic b, with supporting spectroscopic data from iSHELL at NASA InfraRed Telescope Facility. We detect Zeeman signatures in the Stokes V profiles and measure a mean longitudinal magnetic field of ¯Bℓ = 46.3 ± 0.7 G. Rotationally modulated magnetic spots likely cause long-term variations of the field with a slope of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…TOI837 joins a number of other young planetary systems reported from TESS, including DSTucAb, HIP67522b, TOI1726, and AUMicb (Newton et al 2019;Addison et al 2020;Hirano et al 2020;Mann et al 2020;Martioli et al 2020;Montet et al 2020;Palle et al 2020;Plavchan et al 2020;Rizzuto et al 2020;Zhou et al 2020). In the space of planet sizes and ages, the top panel of Figure 11 shows that TOI837 is among the youngest transiting planets known.…”
Section: Discussionsupporting
confidence: 55%
“…TOI837 joins a number of other young planetary systems reported from TESS, including DSTucAb, HIP67522b, TOI1726, and AUMicb (Newton et al 2019;Addison et al 2020;Hirano et al 2020;Mann et al 2020;Martioli et al 2020;Montet et al 2020;Palle et al 2020;Plavchan et al 2020;Rizzuto et al 2020;Zhou et al 2020). In the space of planet sizes and ages, the top panel of Figure 11 shows that TOI837 is among the youngest transiting planets known.…”
Section: Discussionsupporting
confidence: 55%
“…The AU Mic host is an M1 star with a spatially resolved edge-on debris disk (Kalas et al 2004) and at least one transiting planet, AU Mic b (Plavchan et al 2020). This Neptune-size planet is in a 8.5-d prograde orbit aligned with the stellar rotation axis (Martioli et al 2020;Hirano et al 2020;Palle et al 2020). While Plavchan et al (2020) only reported an upper limit on the mass of AU Mic b, Klein et al (2021) measured 17.1 +4.7 −4.5 M ⊕ thanks to infrared observations secured with the SPIRou spectropolarimeter (Donati et al 2020).…”
Section: Introductionmentioning
confidence: 98%
“…The magnetically active star AU Mic has a projected rotational velocity of v sin i * = 7.5 ± 0.9 km s −1 (Martioli et al 2020). A periodic pattern is observed in the TESS S1 data at a reported period of 4.86 d (Plavchan et al 2020), which is ascribable to the presence of spots combined with stellar rotation.…”
Section: Stellar Rotationmentioning
confidence: 95%
“…The sky-projected spin-orbit angle of AU Mic b has been measured by several authors: λ = −2.96 +10.44 −10.30 (Palle et al 2020); λ = 0 +18 −15 (Martioli et al 2020); λ = −4.7 +6.8 −6.4 (Hirano et al 2020); Notes. Time notation follows the ISO-8601 convention.…”
Section: Introductionmentioning
confidence: 99%